Study on Application of Reinforcement Measures for Spillway Foundation on Thick Collapse Accumulation Body - WANG Jun; NING Yu; HUANG Qingfu (Renmin Zhujiang)
The foundation of spillway in the accumulation body is characterized by low bearing capacity,poor stability and large and uneven settlement due to the properties of an accumulation body.In particular,the bottom plate cracking and staggering along the transverse joints caused by uneven settlement of the foundation in the chute section will cause serious damage to the entire chute section under the action of high-speed water flow.Combined with the engineering example,this paper conducts the numerical analysis the vertical settlement displacement distribution and chute structure joint opening of the spillway on the accumulation body by a large finite element software.The research on the improvement effect for spillway foundation strengthened by “replacement method” shows that the method can significantly reduce the vertical settlement of spillway structure.Changing the vertical joints of each section of chute to lap joints can greatly reduce the opening of structural joints.In conclusion,the method proposed in the study is very effective in improving the bearing capacity of spillway foundation and reducing uneven settlement,and is feasible and reasonable in construction and economy, respectively.